(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Income per person in Haryana is fourth highest in India. Haryana’s development organisationshave created 103 separate industrial parks. Haryana’s industrial estates are the product of a collaborativeeffort by the state’s Developers in Haryana, including those working for the state and the Haryana UrbanDevelopment Authority, as well as those working on their own time. The Gurgaon region has developedtremendously over the years, notably in terms of creating a thriving industrial sector. Because of this, itis expected to become a major centre for Haryana’s industrialization. Haryana has its own State ExportPolicy that provides many tax incentives and the most cutting-edge facilities in order to promote exports.A government agency in India called Software Technology Parks of India (STPI) oversees the SoftwareTechnology Park initiative. The Ministry of Communication and Information Technology launched it backin 1991. Power and infrastructure are two areas that the government must invest heavily on. For us tocompete on a worldwide scale, it is essential that we have access to financing at market rates. Since VAThas already been introduced, the federal government should exclude state and municipal fees.